2023
DOI: 10.7759/cureus.40572
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome: Risk Factors and Newer Risk Reduction Strategies

Anita Vincent,
Ngan Thy Chu,
Aashka Shah
et al.

Abstract: Sudden infant death syndrome (SIDS) continues to be one of the top causes of infant death in the U.S. Despite significant public health initiatives focused on high-risk populations to enhance sleep environments and techniques. The SIDS rate has remained stable in recent years. Risk factors and newer risk reduction strategies for SIDS are the focus of this review article. We conducted a comprehensive literature search on Medline, Cochrane, Embase, and Google Scholar until July 2022. The following search strings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Later, a theory was developed (1942, Pende) of "constitutional hyperthymic syndrome" or "Pende syndrome", a condition characterized by an increase in the volume and activity of the thymus from birth, macrosomia and poor development of the genitals during puberty [16]. However, some scientists have insisted that since the thymus is affected within a few days after the disease, it reaches large sizes only if the patient dies suddenly [1,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a theory was developed (1942, Pende) of "constitutional hyperthymic syndrome" or "Pende syndrome", a condition characterized by an increase in the volume and activity of the thymus from birth, macrosomia and poor development of the genitals during puberty [16]. However, some scientists have insisted that since the thymus is affected within a few days after the disease, it reaches large sizes only if the patient dies suddenly [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SIDS in the world is 0.2-1.5 cases per 1000 children. Sudden death in children (without sudden cardiac death syndrome) accounts for 5-10% of all child deaths, which is about 1.3-4.0 per 100,000 population [1]. Thus, the average mortality rate from SIDS per 1000 births is: in Japan -0.25, the Netherlands -0.3, Russia -0.4, Great Britain -2.3, Germany -1.6, Austria -1.0, Italy -0.5, the USA -2.8, in Russia -0.43 per 1000 children [2].…”
Section: Introductionmentioning
confidence: 99%
“…The VRG regulates both the expiratory and inspiratory phases of respiration. Modifications in this specific area might lead to inefficient or superficial respiratory patterns, which can be detected as erratic breathing in persons with epileptic encephalopathies [ 14 ]. The respiratory centers in the pons, specifically the pneumatic and apneustic centers, play a crucial role in regulating the shift from inspiration to expiration.…”
Section: Reviewmentioning
confidence: 99%
“…But still even in developed countries the incidence is high and out of 100 000 live births, at least 1389 died from SIDS with less than 12 months of life. 4 In the USA, estimates have shown that SIDS accounts for 90% of mortality in children up to the 6th month of life. These data prompted several other studies on the risk of SIDS and the need of increasing the population’s knowledge about this event.…”
Section: Introductionmentioning
confidence: 99%